Answer:
-x^3 + x^2 - 2x - 4
Explanation:
You have to subtract
Let o = the polynomial
So you know 2x^3 - x^2 + 4x + 5 - o = x^3 + 2x - 9
Now you do 2x^3 - x^3 = x^3
then you -x^2 + answer = 0
you need to cancel it out
to cancel, you found out that it is x^2
Now you need to make from 4x to 2x.
To do that, you do 4x - 2x and you get 2x
Lastly you need to change -5 to 9. To do that you add -4.
Now since it is subtraction you have to distribute
2x^3 - x^2 + 4x - 5 -(x^3 - x^2 + 2x + 4)
= 2x^3 - x^2 + 4x + 5 - x^3 + x^2 -2x -4
= x^3 -2x + 9